(untitled) (Bangladesh Journal of Anatomy, 2010)
Background: The pyramidal lobe of the thyroid gland is an embryonic remnant of the caudal end of the thyroglossal tract. The pyramidal lobe is formed from normal thyroid tissue. A fibrous band, levator glandulae thyroideae, is found occasionally and extending upwards from the apex of the pyramidal lobe. As all thyroid diseases are found to be present in the pyramidal lobe, the study of the pyramidal lobe bears a great importance. Study design: Cross-sectional descriptive type of study. Place and period of study: Department of Anatomy, Dhaka Medical College, Dhaka from January to December 2008. Materials: The present study was performed on 60 post mortem human thyroid gland (39 male and 21 female) collected from unclaimed dead bodies which were in the morgue under examination in the Department of Forensic Medicine, Dhaka Medical College, Dhaka. Methods: The samples were divided into three age-groups including Group A (10 -20 years), Group B (21- 50 years) & Group C (>50 years) and the pyramidal lobes were studied both morphologically i.e. position, length, breadth, thickness, its association with levator glandulae thyroideae and histologically including presence of thyroid tissue, percentage proportion of parenchyma and stroma. Results: The pyramidal lobe was found in 25 cases out of 60 (41.67%) and situated more on the left side (56%). The mean±SD length of the pyramidal lobe of the thyroid gland was 10.83±0.75 mm in group A, 12.80±3.05 mm in group B and 11.00±1.41 mm in group C. The mean±SD breadth of the pyramidal lobe was 5.50±1.22 mm in group A, 7.60±2.06 mm in group B and 6.75±0.96 mm in group C. The mean±SD thickness of the pyramidal lobe was 3.00±0.00 mm in group A, 3.27±0.59 mm in group B and 3.00±0.96 mm in group C. The levator glandulae thyroideae was found in 12 cases out of 60 (20%) and extended from the apex of the pyramidal lobe to the body of the hyoid bone. The proportion of the parenchyma increases with advancing age upto 50 years. Key Words: morphology; histology; pyramidal lobe; thyroid gland DOI: 10.3329/bja.v7i2.6095 Bangladesh Journal of Anatomy July 2009, Vol. 7 No. 2 pp. 94-100